2018
DOI: 10.1080/1553118x.2018.1510405
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Crisis Communication on Social Media: A Systematic Review of What Research Tells the Practice

Abstract: This study analyzes explicit pieces of advice for effective social media crisis communication given by researchers in various subdisciplines of strategic communication. The themes are identified by a systematic content analysis of peer-reviewed journal articles and conference papers (n = 104) published between 2004 and 2017. Five overall thematic "lessons" are identified and critically discussed. These are that effective social media crisis communication is about: (1) exploiting social media's potential to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 95 publications
2
81
0
6
Order By: Relevance
“…In sum, scholars in the past years have increasingly paid attention to the SMCC research in contexts (Cheng, 2016a;Liu et al, 2015;Tai & Sun, 2007;Taylor & Perry, 2005;Zhu et al, 2017). This field also attracted updated reviews from several scholars such as Cheng (2016a), Eriksson (2018), and Rasmussen and Ihlen (2017). However, none of these studies fully examined the SMCC research in a non-Western context such as contemporary China and a review of the trends and research domains on SMCC in China is lacking.…”
Section: Social-mediated Crisis Communication (Smcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, scholars in the past years have increasingly paid attention to the SMCC research in contexts (Cheng, 2016a;Liu et al, 2015;Tai & Sun, 2007;Taylor & Perry, 2005;Zhu et al, 2017). This field also attracted updated reviews from several scholars such as Cheng (2016a), Eriksson (2018), and Rasmussen and Ihlen (2017). However, none of these studies fully examined the SMCC research in a non-Western context such as contemporary China and a review of the trends and research domains on SMCC in China is lacking.…”
Section: Social-mediated Crisis Communication (Smcc)mentioning
confidence: 99%
“…According to Eriksson (2018), a good systematic review should not only describe directions for theory development and research topics, but also provide implications for practitioners. This review research filled the gap of global public relations literature by presenting lessons for practitioners who are interested in the social media and crisis communication practice in China.…”
Section: Lessons/advice For Practitionersmentioning
confidence: 99%
“…Social media are increasingly becoming a key element of issues management practice and research. Consumers, businesses, government agencies and a host of other entities now use social media platforms to share and gather information (Eriksson, 2018). Such information is "key to ensuring decision making and to increasing their capacity to anticipate, influence and collaborate" (Santa Soriano, Lorenzo Álvarez, & Torres Valdés, 2018, p. 1592.…”
Section: Issues Managementmentioning
confidence: 99%
“…The analysis of the emotional content in the context of isolation due to COVID-19 provides valuable insights into how sentiments are affected by confinement measures and how they are expressed and spread on social media. Previous literature has addressed this issue by focusing on economic and financial crisis impacts [6] and how media content studies have been applied in health crisis management, which have been observed more from the communication point of view and more specifically through a public relations lens [1,4]. Although some authors have already pointed out that feelings expressed in online conversations can be contagious both in a positive [9,15] and a negative way [11][12][13], this work covers the gap by analyzing the public's sentiments in digital ecosystems as a health issue.…”
Section: /05mentioning
confidence: 99%